Digital Skills Challenges Among Indigenous Entrepreneurs in Selangor - Khairudin, Safiyyah; Roddin, Rohayu (Research and Innovation in Technical and Vocational Education and Training, 2024)
The development and integration of digital technologies are essential for the socioeconomic growth of modern civilizations, including the communities of Indigenous Peoples, in this period of rapid globalization and digitalization. However, rural Indigenous Peoples face a digital divide that limits their use of technology for economic betterment. This study explores the digital skill challenges faced by Indigenous Peoples, focusing on internet application access, internet usage skills, motivation, and information sources. It adopts a qualitative approach with a case study design involving five participants, using interviews as the primary data collection method. Thematic analysis with NVIVO11 identified three main themes: digital challenges, operational and marketing challenges in digital business, and the enhancement of digital skills. The study reveals variations in internet access among Indigenous entrepreneurs, high awareness of modern tools, and digital skills. Social media and WhatsApp are vital for marketing, but challenges in logistics, cash payments, and online content approval are significant. Despite efforts to improve digital skills, exposure to and access to the internet remain limited in rural areas. Enhancing internet access, digital skills, and problem-solving strategies are key to adapting businesses to the digital age. This study underscores the need to expand knowledge in digital skills and business, opening avenues for further research, especially in developing digital skills among Indigenous Peoples' students. By highlighting challenges and proposing solutions, it guides the development of inclusive policies to strengthen Indigenous Peoples' communities in the digital era.